A new Idioneura Selys, 1860 for the Brazilian fauna with analysis of the other species (Odonata: Protoneuridae) - Lencioni, F. A.a. (Zootaxa, 2021)
Idioneura Selys, 1860 can be separated from the other Protoneuridae (sensu Tillyard 1917) by a set of characters: angulated frons, presence of the CuP&AA vein, absence of the two subapical teeth in the cercus (present in Lamproneura De Marmels, 2003), and first and second antenodal spaces subequal (first a little longer than second). Here is described a new species, Idioneura furieriae spec. nov., from two females and five males. The new species is compared with I. ancilla Selys, 1860 and I. celioi Lencioni, 2009. Diagnostic illustrations are presented. The major differences between Idioneura species are: in the females, the shape of the highly modified mesostigmal plates and posterior lobe of prothorax; in males, the shape of cerci and paraprocts.